2023
DOI: 10.1002/ppul.26491
|View full text |Cite
|
Sign up to set email alerts
|

Impact of omega‐3 supplementation on children and adolescents patients with cystic fibrosis: A systematic review and meta‐analysis of randomized‐controlled trials

Abstract: Objective: Clinical trial research have provided evidence that omega-3 may have larger potential benefits for treating cystic fibrosis (CF). This study's objective was to assess the impact of three supplementation on pediatric CF patients.Methods: Scopus, PubMed/Medline, Web of Science, Cochrane, and Embase databases were searched from commencement until July 20, 2022 using standard keywords to identify all randomized controlled studies (RCTs) examining the effects of omega-3 supplementation on young patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, changes in anthropometric variables with increases in body weight and height may be expected to occur in children during the growth phase of life, but these increases were greater in the group of DHA-treated participants with statistically significant differences as compared to those in the placebo group. On the contrary, in the analysis of the 12 RCTs included in the systematic review and meta-analysis of Sohouli et al [28], no significant effect of DHA supplementation on anthropometric parameters was observed.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…On the other hand, changes in anthropometric variables with increases in body weight and height may be expected to occur in children during the growth phase of life, but these increases were greater in the group of DHA-treated participants with statistically significant differences as compared to those in the placebo group. On the contrary, in the analysis of the 12 RCTs included in the systematic review and meta-analysis of Sohouli et al [28], no significant effect of DHA supplementation on anthropometric parameters was observed.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies using EPA, DHA, or combinations of EPA, DHA, and LA also reported improvements in lung function parameters [11,13,29,30], but differences in the characteristics of the populations (pediatric and adults), doses of omega-3 administered, and duration of supplementation make comparisons difficult. In a recent systematic review and meta-analysis of 12 RCTs of omega-3 supplementation in CF patients younger than 18 years [28], no significant effect on FEV or FVC was found, considering that the heterogeneity was low and insignificant for these two variables. On the other hand, we found a large variability in FEV 1 , FVC, and FEF 25-75 expressed as % predicted during the year prior to the study, as well as over the 1-year study period.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations